The Impact of Using LEGO Duplo in STEM Education on 8–9 Year Old Students' Conceptual Knowledge of Water: Pilot Study (Training and Practice : Journal of Educational Sciences, 2025)
Introducing STEM education from early childhood is of paramount importance, as this is a sensitive period in establishing children’s interest in science and problem-solving skills. The use of LEGO Duplo in STEM education offers an opportunity to acquire scientific knowledge through experiential learning. The aim of our study was to develop and find a reliable method for detecting changes in students’ complex knowledge about water. In the experiment, a group of students also use a LEGO Duplo set in the process of acquiring knowledge. We chose the word association method as the method of the study. The measurement took place in two steps. After the pre-test, the experimental group participated in LEGO classes, and the control group participated in drawing classes on the role of water in the living and non-living world. After the classes, we measured the change in students' knowledge about water (post-test) in a similar way to the pre-test. According to the results, the conceptual knowledge and knowledge structure of students with LEGO Duplo about water showed a more complex structure compared to the drawing students.
Keywords: LEGO Duplo; STEM education; impact measurement; word association